2023
DOI: 10.1371/journal.pone.0283369
|View full text |Cite
|
Sign up to set email alerts
|

Value of the clinical pharmacist interventions in the application of the American College of Cardiology (ACC/AHA) 2018 guideline for cholesterol management

Abstract: Objectives The study aims to examine the extent to which the updated ACC/AHA management of blood cholesterol guideline (2018) is implemented in practice and to assess the value of the clinical pharmacist interventions in improving physicians’ adherence the guidelines recommendations. Methods We utilized in this study an interventional before-after design. The study was conducted on 272 adult patients who visited the study site internal medicine clinics and were candidates for statin therapy based on the 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Correspondingly, Arca et al observed that out of the total statin-prescribed therapy, only 7.7% comprised high-intensity statin. Moreover, <20% of ASCVD patients (excluding those with recent ACS) were administered high-intensity statin ( 30 ). Other studies also show that high-intensity statin is prescribed to far fewer patients than recommended ( 13 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Correspondingly, Arca et al observed that out of the total statin-prescribed therapy, only 7.7% comprised high-intensity statin. Moreover, <20% of ASCVD patients (excluding those with recent ACS) were administered high-intensity statin ( 30 ). Other studies also show that high-intensity statin is prescribed to far fewer patients than recommended ( 13 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, <20% of ASCVD patients (excluding those with recent ACS) were administered high-intensity statin ( 30 ). Other studies also show that high-intensity statin is prescribed to far fewer patients than recommended ( 13 , 30 ). According to the results, most of the patients with severe hypercholesterolemia were undertreated by moderate-intensity statin, which opposes AHA Guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations